Serum micro-rna profiles in patients with autosomal dominant polycystic kidney disease according to hypertension and renal function - Kocyigit, Ismail (BMC Nephrol, 2017)
BACKGROUND: Autosomal dominant polycystic kidney disease (ADPKD) is a common hereditary disorder with unclear disease mechanism. Currently, overt hypertension and increased renal volume are the best predictors of renal function. In this study, we assessed the usefulness of selected circulating microRNAs (miRs) to predict disease progress in a cohort with ADPKD. METHODS: Eighty ADPKD patients (44.6 ± 12.7 years, 40% female, 65% hypertensive) and 50 healthy subjects (HS; 45.4 ± 12.7, 44% female) were enrolled in the study. Serum levels of 384 miRs were determined by Biomark Real Time PCR. Groups were compared using the limma method with multiple-testing correction as proposed by Smyth (corrected p < 0.01 considered significant). RESULTS: Comparing ADPKD to HS, we found significant differences in blood levels of 18 miRs (3 more and 15 less abundant). Of these, miR-3907, miR-92a-3p, miR-25-3p and miR-21-5p all rose while miR-1587 and miR-3911 decreased as renal function declined in both cross-sectional and longitudinal analysis. Using ROC analysis, an increased baseline miR-3907 in the circulation predicted a > 10% loss of GFR over the following 12 months (cut-off >2.2 AU, sensitivity 83%, specificity 78%, area 0.872 [95% CI: 0.790–0.953, p < 0.001]). Adjusting for age and starting CKD stage using multiple binary logistic regression analysis did not abrogate the predictive value. CONCLUSION: Increased copy numbers of miR-3907 in the circulation may predict ADPKD progression and suggest pathophysiological pathways worthy of further study. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12882-017-0600-z) contains supplementary material, which is available to authorized users.